Neural correlates of aggression in personality disorders from the perspective of DSM-5 maladaptive traits: a systematic review - Kolla, Nathan; Tully, John; Bertsch, Katja (Translational Psychiatry, 2023)
The fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), published in 2013, includes an alternative model of personality disorders (AMPD) focusing on a maladaptive trait model utilized to diagnose several personality disorders. Borderline personality disorder (BPD) and antisocial personality disorder (ASPD) are two conditions categorized by AMPD that exhibit high rates of violence and aggression. Several of the traits outlined in the AMPD, including hostility, impulsivity, risk-taking, and callousness, have been previously linked to aggression in BPD and ASPD. However, to the best of our knowledge, there has never been a synthesis of neuroimaging studies that have investigated links between these traits and aggression in BPD and ASPD. To overcome this gap, we conducted a systematic review under the PRISMA framework to locate neuroimaging articles published since the release of AMPD linking trait anger/hostility, impulsivity, risk-taking, and callousness to aggression in BPD and ASPD. Key findings included the following: i) anger/hostility, associated with alterations in the interplay between prefrontal and subcortical regions (primarily the amygdala), may be a common factor explaining aggressive reactions to response to interpersonal threat or provocation; ii) alterations of fronto-temporal-limbic regions and serotonergic and endocannabinoid signaling systems may link impulsivity to aggression in BPD and ASPD; iii) weaker cortico-striatal connectivity could relate to greater risk taking and greater proclivity for violence. Insufficient evidence from neuroimaging articles was discerned to describe a relationship between callousness and aggression. Overall, results of this review reveal a relative paucity of neuroimaging studies examining AMPD traits relevant to aggression in BPD and ASPD. In addition to encouraging further investigation of neuroimaging markers of AMPD traits linked to aggression, we recommend multi-methodological designs, including the incorporation of other biomarkers, such as hormones and indices of physiological arousal, to fully expand our understanding of aggression in BPD and ASPD.